Transdisciplinarity: A Review of Its Origins, Development, and Current Issues - Jay Hillel Bernstein (Journal of Research Practice, 2015)
Transdisciplinarity originated in a critique of the standard configuration of knowledge in disciplines in the curriculum, including moral and ethical concerns. Pronouncements about it were first voiced between the climax of government-supported science and higher education and the long retrenchment that began in the 1970s. Early work focused on questions of epistemology and the planning of future universities and educational programs. After a lull, transdisciplinarity re-emerged in the 1990s as an urgent issue relating to the solution of new, highly complex, global concerns, beginning with climate change and sustainability and extending into many areas concerning science, technology, social problems and policy, education, and the arts. Transdisciplinarity today is characterized by its focus on “wicked problems” that need creative solutions, its reliance on stakeholder involvement, and engaged, socially responsible science. In simultaneously studying multiple levels of, and angles on, reality, transdisciplinary work provides an intriguing potential to invigorate scholarly and scientific inquiry both in and outside the academy.